A new online-method for the characterization of detached particles while cleaning starch fouling layers. (September 2018) - Sauk, Tobias; Föste, Henning; Augustin, Wolfgang; Scholl, Stephan
Abstract: This work presents a new method for an online measurement of particles detached from a starch fouling layer during a cleaning process. This was achieved by designing the Automated Particle Analyser for Cleaning (APAC) by combining a flow channel with a laser diffraction particle size analyser. A method for the online measurement of particle size for different sets of parameters (flow velocity, temperature and addition of Sodium Hydroxide) was developed, monitoring cleaning progress and behaviour. The influence of the variation of the parameters on the progress of cleaning as well as their balance could be shown. Low temperature or velocity cause increasing cleaning time and vice versa. Overall detachment of small particles indicating cohesive failure could be observed as characteristic for starch based fouling layers. A narrow particle size distribution (PSD) of small particles indicates a cohesive failure and a steady disintegration of the fouling layer from top to bottom. On the contrary a PSD of larger size and broader shape prevails for adhesive failure and detachment of large patches of the fouling layer.